A brief history of payment netting and settlement - Ulrich Bindseil; George Pantelopoulos (IBF - Institut für Bank- und Finanzgeschichte e.V., 2022)
In earlier times, societies relied extensively on "IOUs" ("I owe you") to avert the need for settlement in specie. However, an IOU reliant economy is complex and fraught with financial stability risks. These problems can be overcome through clearing, netting and settlement, either without or with novation. From the perspective of creditors, the most expedient solution is for residual claims to be denominated in a large-scale, riskfree and divisible IOU that is analogous to settlement in specie, but without incurring the disadvantages ofsettlement in preciousmetalcoins. If such solutions are not feasible, it is then desirable that (1) networks of IOUs are simplified through netting, and (2) residual claims are denominated in relatively high-quality claims, which can be readily converted into risk-free positions. The purpose of this paper is to explore how such outcomes have been achieved through the lens of history. As will be shown - whilst netting and settlement with novation is an effective technique to mitigate financial instability risks - it is only through central banks acting as correspondents to the domestic financial system that the drawbacks of the IOU economy can be alleviated to the largest extent in order to attain lean balance sheets, lower credit risk and improved financial stability. At the same time, such a solution also ensures that the financial system remains layered.
Keywords: F33; G21; N20; N24; 330